Pertumbuhan Benih kakao (Theobroma cacao L.) Akibat Pemberian Dosis Limbah Kulit Kopi dan Pupuk Kandang Ayam - Assafaat Hadi, Roni; Amalia, Lia; Sondari, Nunung; Rakhmi Indriana , Kovertina; Mulyana, Hudaya; Budiasih, R; Komariah, Ai (OrchidAgro, 2025)
Cocoa plants, one of the leading commodities in Indonesia, are predicted to become the world's main producer and have the opportunity to compete globally. Alternative planting media to produce optimal growth of cocoa seeds, namely by using agricultural waste in the form of coffee skin waste and fertilizing using chicken manure. This research aims to study the growth of cocoa seeds (Theobroma cacao L.) and their response to doses of coffee skin waste and chicken manure. This experiment was carried out in the screenhouse of the plant experimental garden of the Faculty of Agriculture, Winaya Mukti University at an altitude of 864 m above sea level, carried out in March - June 2023, the experiment used a Randomized Group Design (RAK) with a 4 x 4 factorial pattern with 2 replications, so that 16 treatment combinations and 32 treatment combinations were obtained. experimental unit. The first factor is coffee skin waste with levels k0 = Soil + Coffee Skin Waste (0%), k1 = Soil + Coffee Skin Waste (10%), k2 = Soil + Coffee Skin Waste (20%) and k3 = Soil + Skin Waste Coffee (30%), while the second factor is chicken manure with levels p0 = 0 g/polybag, p1 = 20 g/polybag, p2 = 40 g/polybag and p3 = 60 g/polybag. The results showed that the application of coffee skin waste and chicken manure significantly affected the growth of cocoa plants, especially on the wet weight of the plants with the best dose of 20% for coffee skin waste and 20 g and 40 g for chicken manure.